Review of the work "Writing is needed: The principle of research", by Mario Osorio Marques (Revista Contexto & Educação, 2025)
The review presents the work Writing is necessary: ​​the principle of research, written by the thinker Mario Osorio Marques, written in the form of an open letter addressed to the reader. The objective of the writing is to establish a dialogue with the reader, presenting three of the author's motivations for writing the aforementioned book, as well as any and all writings. The first of these refers to the dimension of writing according to which a possible reader is always assumed, which would give meaning to such a project. The second concerns one of the biggest challenges of writing, which is getting started, with there not being exactly anything like preparation for such a task. The third is that writing cannot be confused with writing, since rewriting will always be necessary and reading will always lead to other possible readings. In this context, the hypothesis that writing is the principle of research gains importance.
Keywords: Search; Writing; Mario Osorio Marques